Social Engineering Approach To Manage Social Environmental Dispute Impacted By Development Plan (Case Study Of Floating Storage Regasification Unit/Fsru Development Plan) - Endang Susilowati; Zaenal Arifin; Sukriyah Kustanti Moerad (JURNAL SOSIAL HUMANIORA (JSH), 2019)
One of the strategic issues in the 2016-2030 SDGs (Sustainable Development Goals), the 7th (seven) goal is clean and affordable energy. The social engineering approach in the social, environmental dispute management of the affected community is an applied research from the case study of the Pasuruan FSRU development plan, namely building floating LNG storage and supporting facilities and facilities at sea, subsea pipeline construction located in the Madura Strait, in the north of the Regency Pasuruan and Sidoarjo Regency, as well as deploying land pipes in Permisan Village, Tambak Kalisogo, and Kupang, Jabon District-Sidoarjo Regency. This research is a descriptive analysis study, which is carried out with cross-sectional, in the study area. The data used in this study are primary and secondary. The primary data from participants in socialization activities of development plan were 33 respondents in Sidoarjo Regency and as many as 25 fishers respondents in Pasuruan City and Regency. Besides, the primary data from the questionnaire to 101 residents affected by land pipeline deployments and 29 people, fishing communities, joined in the HNSI in Pasuruan Regency and City. Often the development plans are hampered by the implementation, including strategic development plans, such as deploying fuel/oil and gas pipes, refineries, FSRUs, etc. due to the issue of dispute in the social environment. This study aims to support ongoing development activities, to underpin decision-making policies. The results of the study show that the community perception factor is very significant towards the development plan that must be managed. Management of these problems is a social engineering approach at the planning stage in the development process by involving various stakeholders ranging from the central government, local government, related agencies, NGOs, local figures and communities affected by the development